2013
DOI: 10.1021/jp408414f
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Dependence of the Optical and Mobility Gaps of Hydrogenated Amorphous Silicon on Hydrogen Concentration

Abstract: The optical absorption properties of hydrogenated amorphous silicon (a-Si:H) are important in solar applications and from the perspective of fundamental materials science. However, there has been a long-standing question from experiment of the dependence of the optical gap on the hydrogen content in a-Si:H. To reconcile this debate, we present density functional theory simulations of models of hydrogenated a-Si:H, with different hydrogen concentrations up to and including full hydrogen saturation. We discuss t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…By contrast, later studies [17][18][19][20][21][22][23] generally claimed that the optical gap of a-Si:H is dependent on H concentration, even though some of 5 them [18 -21] showed that a constant optical gap is achieved at saturation. Our previous work [14] showed for the first time that the optical and mobility gaps of a-Si:H are invariant with H content as long as H saturation is reached.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…By contrast, later studies [17][18][19][20][21][22][23] generally claimed that the optical gap of a-Si:H is dependent on H concentration, even though some of 5 them [18 -21] showed that a constant optical gap is achieved at saturation. Our previous work [14] showed for the first time that the optical and mobility gaps of a-Si:H are invariant with H content as long as H saturation is reached.…”
Section: Introductionmentioning
confidence: 89%
“…we examined H contents of 14%, 15 % and 16.5 % [14] and in this work, we focus on saturation H content of 14 %. This saturated model structure of a-Si:H is relaxed with GGA-DFT.…”
Section: Methods and Preparationmentioning
confidence: 99%
See 3 more Smart Citations